posted by Ashley A. on .
What is the process we follow when multiplying and dividing radical expressions? Explain the process and demonstrate with an example
I think I already explained this to you down below.
I'm sorry but its radical expressions and I wanted a second opiniã3 (x - ã6) = ã3 * x - ã3 * 6 Using a distributive law
= xã3 - ã18 Multiplying radicals
3ãy(3ãy3 + 3ã3) = 3ãy * 3ãy3 + 3ãy * 3ã3 Using a distributive law
= 3ãy3 + 3ã2y Multiplying radicals
= y + 3ã3y Simplifying 3ãy3
I don't know what font you have, but the symbols come out all garbled. try using √ for root and repost.